Islamic accounting mobile game (IAMG): an interactive approach as teaching and learning aid necessary in holistic education for digital society 5.0 / Zanirah Mustafa@Busu ... [et al.] - Mustafa@Busu, Zanirah; Zainal, Noor Saliza; Nik Din, Nik Muniyati; Awang@Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Mohd Firdaus Kozako, Intan Nurul 'Ain; Mat Jusoh, Nor Asmira; Ismail, Mohd Khairul Anuar (2020)
Accounting is an important knowledge in Islam. It is a branch of social knowledge which records financial reports on all activities involving finance. Accounting reports are important for the benefits of the public and those who involved in financial and accounting activities. Nonetheless, the calculation methods found in the Fundamental of Islamic Accounting course are complicated with various concepts and formulas as practiced at various financial institutions. This makes it difficult for students to understand and remember every available formula. Thus, students require new teaching and learning tools to facilitate their learning. Hence, teaching and learning aids are highlighted as one of the most recent transformation for computational learning in Islamic accounting. The main objective of this paper to evaluate the effectiveness of learning through interactive application of Islamic counting game in the classroom. Literature search, documentation of observations, demographic and descriptive methods were also utilized through research surveys, observations and questionnaires on students. These methods were used to collect related data information. The findings reveal that majority of students did not know Islamic Accounting Mobile Game (IAMG). Interestingly after the use of IAMG, students felt that IAMG is good and useful in their studies. Findings showed that the product is accepted by the students and give significant impacts to the students and society.